Acinetobacter baumannii Lipopolysaccharide Influences Adipokine Expression in 3T3-L1 Adipocytes - Yuka Unno; Yoshinori Sato; Satoshi Nishida; Akiyo Nakano; Ryuichi Nakano; Tsuneyuki Ubagai; Yasuo Ono (Mediators of Inflammation)
Acinetobacter baumannii is one of the most important nosocomial opportunistic pathogen worldwide. In addition, obesity has been associated with an increased risk of nosocomial infection, suggesting that there may be an association between A. baumannii and white adipose tissue. However, the effects of A. baumannii on adipocytes have not been well studied at the molecular level. Here, we investigated the potential role of A. baumannii-derived lipopolysaccharides (LPS) as signaling molecules that affect adipocyte functionality. We tested the effect of increasing concentrations of A. baumannii-derived LPS (10, 100, or 1000 ng/mL) on the 3T3-L1 adipocyte cell line. Exposure to LPS was found to increase the expression of several adipokines (e.g., MIP-2, MCP-1, TNF-α, IL-6, lipocalin-2, and FABP4) in 3T3-L1 adipocytes and significantly reduced the expression of leptin and adiponectin. The effects of A. baumannii-derived LPS on MIP-2 expression were similar in comparison with that of LPS prepared from Pseudomonas aeruginosa and Escherichia coli in our cell culture-based system. This study suggests that A. baumannii-derived LPS functions as a signaling molecule that impacts the inflammatory function of white adipose tissue on the level of gene expression.